Energy engineering : proceedings of CAETS 2015 Convocation on Pathways to Sustainability - Raghavan, K. V.; Ghosh, P., 1947- (Springer, 2017)
This book contains the proceedings of CAETS 2015 Convocation on 'Pathways to Sustainability: Energy, Mobility and Healthcare Engineering' that was held on October 13-14, 2015 in New Delhi. This 3 volume proceedings provide an international forum for discussion and communication of engineering and technological issues of common concern. This volume talks about 'Energy' and includes 22 chapters on diverse topics like renewable energy, advances and applications of bio-energy and bio-refinery, energy options and scenarios, wind energy for buildings and transportation, etc. The contents of this volume will be useful to researchers, professionals, and policy makers alike.